Review on inorganic pollutants in stormwater runoff of non-metal roofs - Degenhart, Julia; Helmreich, Brigitte (Frontiers in Environmental Chemistry, 2022)
Metal roofs have always been in focus as a source of contamination of stormwater runoff. However, other roofing materials are also suspected of emitting metals and other inorganic substance with the stormwater runoff. Hence, this review focuses on the impact of commonly used non-metal roofs – vegetated and non-vegetated – on stormwater runoff quality. Results from over 40 studies were compiled and assessed to gain an overview of substances in runoff from nine roofing types with a special focus on green roofs. Concentrations of 27 substances including nutrients, heavy metals and other inorganic substances were compared. Results show that the nine regarded roof types can be a potential source for these substances in runoff. Limit values for groundwater protection are exceeded especially for PO43-, Cu, Pb, and Zn for some roofing materials. As the concentrations vary strongly for different parameters no roofing material can be identified as clearly superior or inferior to the others. Green and flat gravel roofs act as a sink for NH4+ and can retain some heavy metals. Elevated heavy metal concentrations were found in runoff from wood shingle roofs treated with preservative chemicals and in runoff from most roofing types usually due to the used gutter materials. Green roof runoff shows high concentrations of Ptot, PO43-, Na, K, Ca, and Mg. The concentrations depend strongly on the green roof age, the used growth substrate and applied fertilizers. Besides the roofing materials, external factors dependent on the location (rural or urban site) influence the runoff quality. Runoff from the analyzed roofs must be seen as a diffuse source of environmental pollution and requires appropriate treatment before it is released into the environment or used for further applications. The applied roofing materials and installations should be chosen with great care regarding the stormwater runoff quality.